ANALYSIS OF COACHING AND MENTORING TOWARDS EMPLOYEE PERFORMANCE AT LOTTE GROSIR MANADO - Pamelia Sherenn; Josep B. Kalangi; Emilia M. Gunawan (Universitas Sam Ratulangi, 2023)
This study aims to analyze and find out if coaching and mentoring have an effect on Employee Performance at Lotte Grosir Manado’s employees. This research is using quantitative method. It will explain the relationship of variables through Causal analysis in the scale method between two continuous independent variables and one dependent variable. Researcher distributed questionnaires and the sample used was 30 respondents from fresh and bakery division. The result showed both coaching and mentoring simultaneously have a positive effect on Employee Performance at Lotte Grosir Manado. But coaching partially do not has a significant effect on employee performance, but mentoring has a significant on employee performance. Based on the results it can be said that Coaching and Mentoring have an important role in effecting Employee Performance Keywords: coaching, mentoring, employee performance